Case report and literature review: management of Paxlovid (nirmatrelvir/ritonavir)-induced acute tacrolimus toxicity in a patient with systemic lupus erythematosus - Jiang, Chenxiao; Yan, Xiaodi; Xia, Peng; Luo, Xuemei; Zheng, Haoyue; Tong, Hanwen; Liu, Yun; Zhu, Huaijun; Xu, Peng; Wang, Jun (Frontiers in Pharmacology, 2024)
Despite the availability of effective vaccines and treatments for SARS-CoV-2, managing COVID-19 in patients with systemic lupus erythematosus (SLE) remains challenging, particularly considering drug-drug interactions (DDIs). Here, we present a case of DDIs between Tacrolimus (Tac) and nirmatrelvir/ritonavir (NMV/r) in a 32-year-old male with SLE. Following self-administration of NMV/r and resumption of Tac after 5 days, the patient experienced acute nephrotoxicity and neurotoxicity, accompanied by supratherapeutic Tac levels, despite Tac being withheld during NMV/r. The primary cause of this acute toxicity is attributed to ritonavir's inhibitory effect on both CYP3A4 enzymes and P-glycoprotein. Upon admission, Tac was discontinued, and supportive therapies were initiated. Phenytoin, a CYP3A4 inducer, was administered to lower Tac levels under the guidance of clinical pharmacists, effectively alleviating the patient's acute toxic symptoms. The half-life of Tac during the treatment of phenytoin was calculated to be 55.87 hours. And no adverse reactions to phenytoin were observed. This case underscores the persistence of enzyme inhibition effects and demonstrates the effectiveness and safety of utilizing CYP3A4 enzyme inducers to mitigate Tac concentrations. Furthermore, it emphasizes the importance of healthcare providers and patients being vigilant about DDIs in Tac recipients. Lastly, it highlights the indispensable role of pharmacist involvement in clinical decision-making and close monitoring in complex clinical scenarios. Although our findings are based on a single case, they align with current knowledge and suggest the potential of individualized combination therapy in managing challenging COVID-19 cases in immunocompromised patients.